National blue carbon assessment in Spain using InVEST: Current state and future perspectives - González-García, Alberto; Arias, Marina; García-Tiscar, Susana; Alcorlo, Paloma; Santos-Martín, Fernando (Ecosystem services, 2022)
•High-resolution spatial distributions of coastal blue carbon were mapped in Spain.•Carbon storage and sequestration from marine phanerogams have been quantified and mapped in Spain.•82% of carbon storage and sequestration by marine phanerogams is under Natura 2000 protected sites.•Under the current management model Spain will lose 24% of carbon stored by 2050.•The economic estimation of coastal blue carbon represents approximately 0.7 of the national GDP. Coastal and marine ecosystems supply multiple services in which human well-being is highly dependent. However, high-resolution spatial distribution studies of marine ecosystem services are scarce, even if it is known that this information is needed to better manage and conserve these ecosystems. With the aim of filling this gap, in this study we have: (1) mapped and assessed the current capacity of marine phanerogams (Posidonia oceanica, Cymodocea nodosa, Zostera noltii, Zostera marina, and Halophila decipiens) to store and sequester blue carbon in Spain; (2) mapped and assessed the future capacity of marine phanerogams to store and sequester blue carbon under three plausible futures; and (3) assess the economic implications of these scenarios. Our results are based on the InVEST Blue Carbon model and exhibit high spatial resolution (100 m/pixel) of carbon stored in marine phanerogams. We found that 82% of carbon storage and sequestration by marine phanerogams is currently managed within Natura 2000 areas. However, results from the modeled future scenarios indicate a constant decrease in the amount of carbon stored in these ecosystems by 2050 (24% lost in the business-as-usual scenario). The economic impact of these losses is equivalent to 17,974 million € (around 1.6% of the Spanish GDP). Finally, we consider that a transformative management change is needed to conserve marine phanerogams in Spain, and we discuss the importance of the Natura 2000 Network in managing marine ecosystems and their services in the near future.